Understanding solutions as technology-driven business innovations. Issue 3 (1st May 2015) - Chiara Cantù, Prof Annalisa Tunisini, Dr; Windahl, Charlotta
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide a better understanding of the innovation challenges firms face when developing and commercialising solutions in the capital goods sector; challenges related to the interdependencies between the supplier/innovator and the customers, as well as the solution's impact on their competencies and activities. Design/methodology/approach – This paper draws upon the emerging body of literature on solutions and established frameworks within innovation management literature. It explores a real-time longitudinal case study of "Alpha" (an international specialist in centrifugal separation, heat exchange and fluid handling), including an R&D project, the project's transformation into an internal corporate venture and the years of the venture up until its integration into the corporate. Findings – This paper characterises solutions as involving product and business innovation. By clarifying the differences between how the solution affects the customers and the suppliers, the use of the proposed framework develops a deeper understanding of the obstacles and difficulties involved in solution innovation. Research limitations/implications – Although some customers were interviewed in this study, a more in-depth study of the customers and the actors within the business network would provide further insight into solution innovations. Merging the two discussions on co-creation and role of users in innovation could provide an avenue for fruitful research within this area. Practical implications – This paper provides a framework for deconstructing solution innovation, enabling detailed comparison between the innovation's impact on both suppliers' and customer's competencies. Such a tool is helpful for increased understanding of how to facilitate internal and external acceptance for a disruptive and radical business innovation. Originality/value – This paper links the development and commercialisation of solutions with established innovation frameworks. Understanding solutions as technology-driven business innovations provides a multifaceted and complex perspective on solutions and contributes to better understanding of radical business innovations.